2001
DOI: 10.33584/jnzg.2001.63.2412
|View full text |Cite
|
Sign up to set email alerts
|

Searching for clover root weevil (Sitona lepidus) resistance/tolerance - A progress report

Abstract: The decimation of white clover in Waikato and Bay of Plenty pastures owing to the invasion clover root weevil (CRW) initiated an extensive screening of legume germplasm to identify plant material that could survive and remain productive under high CRW pressure. A total of 50 000 plants from 275 lines and six species, were planted on seven commercial farms and evaluated for tolerance/ resistance to CRW under conventional farming practices. Plant productivity and level of CRW damage were both highest on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Data on clover root weevil tolerance is adapted from Eerens et al (2001) and includes 20 white clover cultivars that were bred in New Zealand or were bred overseas but are commercially available in New Zealand.…”
Section: Methodsmentioning
confidence: 99%
“…Data on clover root weevil tolerance is adapted from Eerens et al (2001) and includes 20 white clover cultivars that were bred in New Zealand or were bred overseas but are commercially available in New Zealand.…”
Section: Methodsmentioning
confidence: 99%
“…Red clover Trifolium pratense L. has been observed to persist longer than white clover Trifolium repens L. during field screening of legumes for tolerance of Sitona lepidus Gyllenhal (Coleoptera: Curculionidae) (Eerens et al , 2001; Cooper et al , 2003). Although this is thought to be related to adult feeding preferences, mixed results have been reported in laboratory studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, Murray (1996) repor ted less feeding on red clover than white clovers (cultivars not specified), and less egg laying by CRW on red clovers. New Zealand field studies have also shown that Lotus is not a prefer red host plant for CRW and that shoot damage on red clover is intermediate between Lotus and white clover (Eerens et al 2001). Recent research under controlled conditions at Ruakur a has confirmed tha t CRW adults str ongly prefer white clover to red clover (Gerard & Crush 2003).…”
Section: Introductionmentioning
confidence: 99%